2011
DOI: 10.1603/en10225
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dependence, Dispersion, and Sequential Sampling ofAnaphothrips obscurus(Thysanoptera: Thripidae) in Timothy

Abstract: The spatial distribution and dispersion of Anaphothrips obscurus (Müller) (Thysanoptera: Thripidae) was examined with the goal of establishing a sequential sampling plan for this pest in timothy, Phleum pratense L. (Poaceae). Approximately 16 different California timothy fields were sampled twice yearly from 2006 to 2008 using direct observation and the beat cup method. For direct observation, the number of thrips on each leaf of the plant was counted. For the beat cup method, tillers were tapped into a cup an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“…We found that the abundance of thrips on suckers was first positively correlated with the height of the sucker, suggesting that the population dynamics of E. brevisetis may be resource dependent as has been shown for the thrips Anaphothrips obscurus (Reisig et al. ). An alternative hypothesis is that the number of thrips on the banana plant is dependent on the number of young leaves.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We found that the abundance of thrips on suckers was first positively correlated with the height of the sucker, suggesting that the population dynamics of E. brevisetis may be resource dependent as has been shown for the thrips Anaphothrips obscurus (Reisig et al. ). An alternative hypothesis is that the number of thrips on the banana plant is dependent on the number of young leaves.…”
Section: Discussionsupporting
confidence: 70%
“…The thrips were enumerated by direct, visual observation because this method has been proven to be effective (Delattre and Torregrossa ; Reisig et al. ). At each observation time, we also collected information on the height of the sucker, the phenological status (pre‐flowering or flowering) of the mother plant and the presence of weeds in a 1‐m radius around each banana plant.…”
Section: Methodsmentioning
confidence: 99%
“…en aguacate (Solares et al, 2011), Thrips spp. asociados al arándano (Rhodes et al, 2011), Thrips palmi Karny (Cho & Lee 2000) y Anaphothrips obscurus Müller (Reisig et al, 2011).…”
Section: Discussionunclassified
“…Variogram analysis, developed for geology and mining, has more recently been adapted for environmental and ecological studies. It has been used to describe spatial structure of western tarnished plant bugs, Lygus hesperus (Knight), in cotton (Carriere 2006); sunßower midge, Contarinia shulzi Gagne, in sunßower, Helianthus annuus L (Hodgson 2004); coffee berry borer, Hypothenemus hampei Ferrari, and leaf minor, Leucoptera coffeella, in coffee, Coffea arabica L. (Alves et al 2011); and grass thrips, Anaphothrips obscurus (Mü ller), in timothy, Phleum pratense L. (Reisig et al 2011). Results from MoranÕs I and variogram analysis can be used to further analysis, such as kriging interpolation (Alves et al 2011, Reisig et al 2011.…”
mentioning
confidence: 99%